Effects of dietary linolenic acid on growth, fatty acid composition, immune function and antioxidant status of juvenile blunt snout bream, Megalobrama amblycephala. (7th June 2017) - Zhang, Wuxiao; Sun, Shengming; Ge, Xianping; Xia, Silei; Zhu, Jian; Miao, Linghong; Lin, Yan; Liang, Hualiang
Abstract: A nine‐week feeding trial was performed to determine the dietary linolenic acid (LNA; 18:3n–3) requirements of juvenile blunt snout bream. Six iso‐nitrogenous, semi‐purified diets were prepared with different concentrations of LNA (0–25 g/kg). Dietary LNA had no significant effects on survival rate. However, final fish weight, weight gain (WG), specific growth rate (SGR) and feed efficiency ratio (FER) increased with increasing dietary LNA concentrations up to 20 g/kg. Dietary LNA increased muscle LNA and total n‐3 polyunsaturated fatty acid (PUFA) contents, but decreased total saturated fatty acid content. Fish fed 20 g/kg LNA had the highest plasma alkaline phosphatase activity, total protein, albumin and white blood cell count levels. Additionally, fish fed 20 g/kg LNA had higher triglyceride levels than control fish. Plasma glucose increased with increasing dietary LNA concentrations. Superoxide dismutase and glutathione peroxidase activities significantly increased with increasing dietary LNA concentrations up to 15 g/kg. Based on SGR and FER, the optimal dietary LNA requirements of juvenile blunt snout bream were 17.5 and 15.6 g/kg respectively.